2002
DOI: 10.1103/physrevb.66.195325
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear dynamics in far-infrared driven quantum-well intersubband transitions

Abstract: We study the effect of many-body interactions on the collective response of confined electrons in doped quantum-well ͑QW͒ heterostructures to intense far-infrared radiation. Absorption line shapes are computed both by numerically integrating the equations of motion and by using the appropriately time-averaged equations. For a two-subband double-QW system, optical bistability and period-doubling bifurcations are observed and their parameter range of activity is given. For a three-subband asymmetric triple-QW sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…In related experiments, intersubband transitions in intense laser fields have been studied experimentally [5][6][7][8] and theoretically. [9][10][11][12][13][14] In theoretical works, the effects of electron-electron interactions have been included mainly in the Hartree approximation by, e.g., Zaluzny 10 and Birnir and Galdrikian. 13 The effect of the exchange and correlations were studied using semiconductor Bloch equations ͑SBE's͒͑ exchange only͒ 11,12,14,15 and the time-dependent density functional approach.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In related experiments, intersubband transitions in intense laser fields have been studied experimentally [5][6][7][8] and theoretically. [9][10][11][12][13][14] In theoretical works, the effects of electron-electron interactions have been included mainly in the Hartree approximation by, e.g., Zaluzny 10 and Birnir and Galdrikian. 13 The effect of the exchange and correlations were studied using semiconductor Bloch equations ͑SBE's͒͑ exchange only͒ 11,12,14,15 and the time-dependent density functional approach.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14] In theoretical works, the effects of electron-electron interactions have been included mainly in the Hartree approximation by, e.g., Zaluzny 10 and Birnir and Galdrikian. 13 The effect of the exchange and correlations were studied using semiconductor Bloch equations ͑SBE's͒͑ exchange only͒ 11,12,14,15 and the time-dependent density functional approach. 16 The effects of electron-electron correlations in quantum dots in intense laser field have also been studied using exact diagonalization techniques.…”
Section: Introductionmentioning
confidence: 99%
“…For semiconductor heterostructures, the nonlinearity of inter-subband absorption was predicted and studied since late 80s [28][29][30][31][32][33] and absorption bistability has been long sought. [34][35][36][37] In this work, we present theoretical and experimental studies of nonlinear absorption effects for a strongly correlated electron system on liquid helium surface. A short account of the results appeared earlier.…”
Section: -14mentioning
confidence: 99%
“…Most previous theoretical studies of nonlinear ISB dynamics were based on the semiconductor Bloch equations (SBE) in Hartree [11]- [13] or exchange-only [14]- [16] approximation. These studies showed that the collective ISB electron dynamics is strongly influenced by depolarization and exchange-correlation (xc) manybody effects.…”
mentioning
confidence: 99%
“…The present study deals with a popular simplification of the ISB SBE: the 2-level rotating-wave approximation (RWA) [11]- [13], which was used by Za użny [11] to derive analytical expressions for nonlinear ISB photoabsorption. The 2-level RWA works well for symmetric quantum wells, but we will demonstrate numerically that it breaks down when the system becomes asymmetric under the influence of DC electric fields.…”
mentioning
confidence: 99%